Electrical Muscle Stimulation in Swim Training: A Performance and Safety Evaluation In Novice Swimmers - Al Ghumayda; Sulastri, Afianti; Rahmi, Upik; Maulana, Boyke (Universitas Pelita Harapan, 2025)
Electrical Muscle Stimulation (EMS) activates muscle fibers by applying electrical currents via electrodes to targeted muscles and is widely used by competitive athletes. Despite its board application, the specific effects of EMS on swimmere remain underexplored. This study evaluates the effectiveness of EMS Butterfly in enhancing speed and performance among novice swimmers compared to conventional training. A single-group pre-post experimental design was conducted with 21 beginer swimmers (treatment group: 14; control group: 7). The treatment group received EMS for 15 minutes before regular training, twice weekly for once month. Speed was assessed by timing a 50-meter freestyle swim using a calibrated digital stopwatch. Statistical analysis included paired t-test and Shapiro-Wilk for normality. All participants were matched for ability and fitness and supervised by coaches and sport nurses. The treatment group demonstrated a mean time reduction of 14.0 seconds (95% CI: 3.63, 21.85), which was statistically significant (p<0.05), whereas the control group improved by 3.7 seconds (95% CI: -7.87, 15.29; p>0.05). The difference between groups was stattiscally significant. These findings indicate that EMS Butterfly is effective for improving novice swimmers' performance, supporting its integration into training programs. Further research is recommended to evaluate long-term effects across performance levels.